A questão indígena Raposa/Serra do Sol na mídia escrita: do estereótipo ao racismo - Barbosa, Elisangela Dias (2010)
The aim of this research is to treat the indigenous issue Raposa/Serra do Sol in the print media. To achieve this, the study investigated how the indigenous populations of Raposa/Serra do Sol have been represented in the journalistic material produced by the newspaper Folha de Boa Vista, covering the incident occurred on May 5th 2008 in the Plantation Depósito, situated in the indigenous reservation under dispute. The importance given to this incident is due to the way the news has been shaped by this newspaper, which characterized it as an episode between indigenous and plantation workers. According to what has been said, we have chosen for our corpus four articles which refer to this incident. Considering that the indigenous people are a social minority and that the media discourse is an elite discourse capable of influencing the public opinion and increasing stereotypes and racism, we have based our research on theoretical parameters derived from Critical Discourse Studies, according to Teun A. Van Dijk‟s thought, using also Walter Lippmann‟s critical and philosophical approach as well as Patrick Charaudeau‟s methodological parameters of discourse in the media context. The analysis of the corpus has highlighted the following points: a) the media, as symbolic elite, in their news discourse tend to exclude the minorities; b) the procedure used by the newspaper Folha de Boa Vista, in the analysed journalistic materials, is adverse to the indigenous people and tends to feed stereotypes of the rebellious indigenous and to reproduce racism in the society of Roraima; c) the Folha de Boa Vista, by favouring the non-indigenous people, reveals itself as unprepared to approach interethnic topics in contexts such as the Amazon